Anti-Inflammatory Activity of Human Lens Crystallin Derived Peptide - Muralidharan, Anuraag; Tender, Tenzin; Shetty, Pallavi K; Mutalik, Srinivas; K., Krishna S.; Hariharapura, Raghu Chandrashekar (Current Drug Delivery, 2021)
Background: Inflammation has become the culmination point for several chronic diseases like skin diseases, asthma, neurological disorders, cancer, and cardiovascular disorders. Mini αA-crystallin peptide, identified from a highly conserved region of human lens protein αA-crystallin, is known to have a chaperone-like function; hence, it has generated interest in exploring the anti-inflammatory potential of the peptide. Objective: The objective of the study was to evaluate the anti-inflammatory potential of mini αA chaperones using in vitro, ex-vivo, and in vivo models. Methods: The peptide was tested for its phosphodiestarase4 B inhibition, anti-inflammatory and free radical scavenging abilities in HaCaT cells. Carbopol gel formulations with varying concentrations of mini αA-crystallin peptide and diclofenac sodium were prepared and optimized. Skin permeation studies of prepared formulations were carried out on excised abdominal skin of Wistar rat using a vertical type diffusion cell. Carrageenan induced rat paw oedema model was used for determining the anti-inflammatory potential of the peptide in prepared gel formulation with or without diclofenac sodium. Results: The peptide exhibited appreciable free radical scavenging and weak PDE4B inhibition. Gel formulation with 1% Tween-80, 1% carbopol, and 10% ethanol showed better permeation compared to other formulations. The in vitro skin permeation studies revealed good improvement in permeation characteristics of diclofenac and peptide from the gels. The peptide was retained within the skin tissue, which is an ideal requirement for the delivery of an anti-inflammatory topical formulation. In preclinical anti-inflammatory studies, gel formulation containing mini αA-peptide and diclofenac sodium showed a significant decrease in paw volume compared to other combinations tested. Conclusion: The study revealed the additive effect in anti-inflammatory activity by combining mini-αA peptide and diclofenac sodium which effectively reduced the inflammation.
Keywords: peptide skin permeation